Examining Relations of Driver's Self-Confidence Level with Automotive Instrument Cluster Reading Performance. (September 2014) - Kim, Sang-Hwan; Xu, Mengyao; Harrelson, Heather; Pedamallu, Rama Kishore Akshay; Weiss, Brian; Escobar, Claudia
The objective of this study is to understand which mechanism of instrument cluster reading performance is associated with drivers' self-ratings on confidence level relating to general mental/physical abilities and daily life habits as well as age and gender. Sixty drivers, consisting of forty elderly drivers and twenty young drivers, participated in the study. Participants completed a self-assessments questionnaire, which asked about their level of self-confidence in various aspects of their life, as well as a controlled experiment using a driving simulator to collect actual reading performance including speed and accuracy as well as eye movement profile for the information reading. Individual data analysis on each of subjective ratings and reading performance confirmed senior drivers' degraded specific aspects of self-confidence level and reading performance such as longer information acquisition and processing time. Consequently a structural equation model revealed how self-confidence level and reading performance are related by mediation of age.